The Concept of Ethno Parenting Early Childhood in The Samawa Tribe - Zubaedah, Siti; Hafidz, Nur; Ayu Lestari, Yuyun; Fatmawati, Emi (International Proceedings of Nusantara Raya, 2022)
Indigenous culture has always been an interesting thing to research. This is because certain ethnic groups are located in Sumbawa, such as the Samawa tribe. This tradition that has been attached will be difficult to remove. The Samawa tribe has ethno parenting for early childhood to do things from an early age with a tradition of trust, such as Pay Intentions, Biso' Tian, Besunat, Entek Beng, and Bequris. These five things are done from an early age in parenting since childhood which has become a Sumbawa culture. From here, this researcher focuses on analyzing the concept of ethno-parenting for early childhood in the Samawa tribe. This study uses a qualitative descriptive study in West Nusa Tenggara which is located in the Sasambo tribe and is divided into three tribes, namely the Sasak tribe, the Samawa tribe, and the Mbojo tribe. This research uses observation, interview, and documentation techniques. The data source uses secondary data and primary data. Observations in 5 Samawa families in parenting, interviews with parents who use the five traditions in parenting, documentation in the form of photos and other writings as supporting references for researchers. The results of this study indicate that there are five ethno-parenting activities for early childhood in the Samawa tribe, namely, (1) Pay Intentions, (2) Biso' Tian, (3) Besunat, (4) Entek Beng, and (5) Bekuris. These five rituals are carried out by the Samawa tribe in the development of children from an early age to maximize their potential, and skills, and preserve the culture of the Samawa tribe